SHARIA-COMPLIANT CREDIT CARD EXPOSURE AND UTILISATION IN THE GROWING DIGITAL ECONOMY - Laily Dwi Arsyianti; Adelia Adelia (Bank Indonesia, 2019)
Many cashless payment tools have been introduced into the Indonesia market in the form of electronic money cards. The Sharia-compliant credit card is a traditional electronic payment tool, but is provided by only two Islamic finance institutions among the many in Indonesia. The increase in Sharia-compliant credit card transactions over time may mean banks are exposed to non-performing risk. Customer behaviour varies in the use of such cards, and this may cause unpredicted results with regard to card performance. Therefore, the purposes of this study are: 1) to identify the behaviour of Sharia-compliant credit card users and 2) to analyse the factors which influence this behaviour. The primary data were gathered by distributing questionnaires with a total sample of 170 respondents and were analysed by employing structural equation modeling. The research shows that gender, age, and education influence perceived behaviour control, and that expenditure influences subjective norms. Customers’ attitudes, subjective norms and perceived behaviour control are proven to influence their intentions, while customers’ intentions, perceived behaviour control and income influence their behaviour when using Sharia-compliant credit cards. For further sustainable inclusive growth, issuers should pay attention to education for specific audiences.